1994
DOI: 10.1093/carcin/15.11.2449
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbon–DNA adducts in smokers and their relationship to micronutrient levels and the glutathione-S-transferase M1 genotype

Abstract: Sixty-three male cigarette smokers were entered into a cross-sectional study to determine whether inverse associations existed between polycyclic aromatic hydrocarbon (PAH)-DNA adduct levels and intake/serum levels of vitamin A, vitamin C and vitamin E. Associations between PAH-DNA adducts and intakes of carotene, as well as serum levels of beta-carotene, were also determined. Fasting blood samples were collected for assays of PAH-DNA adducts in circulating mononuclear cells, plasma cotinine and serum levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…DNA adducts were found higher in GSTM1 null subjects in the EPIC -Italy study, and were inversely associated with the consumption of fresh fruit, vegetables, olive oil and antioxidants (Palli et al, 2000). Earlier studies suggested an important role for dietary antioxidants on DNA adduct results in smokers (Grinberg-Funes et al, 1994;Mooney et al, 1997). Given the significant role dietary constituents are now thought to play in lung cancer (Williams and Sandler, 2001) further work in this area is needed.…”
Section: Metabolic Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA adducts were found higher in GSTM1 null subjects in the EPIC -Italy study, and were inversely associated with the consumption of fresh fruit, vegetables, olive oil and antioxidants (Palli et al, 2000). Earlier studies suggested an important role for dietary antioxidants on DNA adduct results in smokers (Grinberg-Funes et al, 1994;Mooney et al, 1997). Given the significant role dietary constituents are now thought to play in lung cancer (Williams and Sandler, 2001) further work in this area is needed.…”
Section: Metabolic Polymorphismsmentioning
confidence: 99%
“…Glutathione S-transferases and cytochrome P4501A1 Although early studies suggested a role of GSTM1 deficiency in aromatic-hydrophobic DNA adduct levels (Ryberg et al, 1994;Grinberg-Funes et al, 1994;Shields et al, 1993;Kato et al, 1995) these studies were criticized (Cuzick, 1995) for not defining cigarette smoking exposure adequately and for not having sufficient size to adjust for potential statistical artifacts. Continued work on the GSTs has appeared (Table 1) and more recent studies have included polymorphism of the GSTT1 and GSTP1 genes.…”
Section: Metabolic Polymorphismsmentioning
confidence: 99%
“…In humans, tobacco smoking leads to increased adduct formation in target tissues such as the lung (Phillips et al, 1988;Schoket et al, 1998;Wiencke et al, 1995) and in surrogate tissues such as the blood (Tang et al, 1995;Vineis et al, 1994;Wiencke et al, 1995). Evidence exists that carcinogen-DNA adduct levels are affected by genetic predispositions (Badawi et al, 1995;Grinberg-Funes et al, 1994;Kato et al, 1995;Pastorelli et al, 1998;Rojas et al, 1998;Ryberg et al, 1997;Stern et al, 1993). Several types of studies indicate that carcinogen-DNA adducts are related to cancer risk.…”
Section: Pathobiological Effects and The Clues To Etiologymentioning
confidence: 99%
“…Fourteen out of 38 studies on exposure to PAHs reported the influence of GSTM1 null (66,102,114,118,122,123,130,132,133,138,142,151,154,156) and, of the 20 studies also examining the genotypes of phase 1 enzymes activating PAHs (CYP1A1), 9 noted the influence on DNA adduct level of mutant genotype CYP1A1 (greater activity) alone or in combination with GSTM1 null (102,122,127,132,(152)(153)(154)(155)157). In four of eight studies on cigarette smoke exposure, in which NAT2 or NAT1 genotypes were considered, increased adduct levels in subjects with the slow acetylator genotype were reported.…”
Section: Dna Adductsmentioning
confidence: 99%